2019
DOI: 10.3390/ijms21010102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trans-Cinnamaldehyde on Methicillin-Resistant Staphylococcus aureus Biofilm Formation: Metabolic Activity Assessment and Analysis of the Biofilm-Associated Genes Expression

Abstract: The effects of trans-cinnamaldehyde (TC) on transcriptional profiles of biofilm-associated genes and the metabolic activity of two methicillin-resistant Staphylococcus aureus (MRSA) strains showing a different degree of adherence to polystyrene, were evaluated. Metabolic activity of S. aureus in biofilm was significantly decreased in the presence of TC at 1/2 minimum biofilm inhibition concentration (MBIC). Expression levels of the genes encoding laminin binding protein (eno), elastin binding protein (ebps) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Serial twofold dilutions of honey were prepared to obtain concentrations ranging from 50% to 1.56%. Determination of MBIC and MBEC of manuka honey was carried out according to method described earlier by Kot et al 35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial twofold dilutions of honey were prepared to obtain concentrations ranging from 50% to 1.56%. Determination of MBIC and MBEC of manuka honey was carried out according to method described earlier by Kot et al 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Control of bacterial growth was performed in the wells with bacterial cell suspensions without manuka honey, as well as control of sterility of the media (wells without addition of bacterial cell suspension). Bacterial cell viability in biofilms, after the appropriate incubation period, was determined by the resazurin microtiter-plate assay as described earlier 35 . Metabolic assay is excellent for the quantification of bacterial viability in biofilm, and the amount of metabolite produced by a biofilm depends on both the metabolic activity of the individual bacteria and the number of live bacteria in the biofilm.…”
Section: Methodsmentioning
confidence: 99%
“…In regard to EO activity on bacterial genes, it has been found that rosemary and Baccharis psiadioides EO have shown a bacteriostatic effect that impacts the development and functions of bacterial cells of L. monocytogenes by upregulating and downregulating stress and virulence genes such as actA , and hly , thus reducing bacterial virulence [ 136 ]. In addition, by using scanning electron microscopy, qPCR, and a 96-well plate method, cinnamon oil has been found to have activity against the expression of icaA gene and biofilms of S. epidermidis [ 137 ]. Furthermore, confocal laser scanning microscopy (CLSM) has shown that cinnamaldehyde is able to kill the tested bacteria, thus indicating its effectiveness in biofilms [ 137 ].…”
Section: Recent Approachesmentioning
confidence: 99%
“…In addition, by using scanning electron microscopy, qPCR, and a 96-well plate method, cinnamon oil has been found to have activity against the expression of icaA gene and biofilms of S. epidermidis [ 137 ]. Furthermore, confocal laser scanning microscopy (CLSM) has shown that cinnamaldehyde is able to kill the tested bacteria, thus indicating its effectiveness in biofilms [ 137 ]. All these findings prove that different EO can modulate gene expression by upregulating and downregulating stress and virulence genes of different microorganisms.…”
Section: Recent Approachesmentioning
confidence: 99%
“…Trans -cinnamaldehyde (TC) is an aromatic aldehyde, which predominately exists in cinnamon essential oils [20, 21]. It has been shown to have antimicrobial and antibiofilm activities against a wide range of bacterial pathogens including Pseudomonas aeruginosa [22, 23], Escherichia coli [24, 25], Staphylococcus aureus [26,27], Staphylococcus epidermidis [28], and Streptococcus mutans [29]. There is some evidence to show that TC inhibits growth of E. faecalis [30, 31], without inducing an adaptive phenotype [31].…”
Section: Introductionmentioning
confidence: 99%